The PIAAC longitudinal study in Germany: rationale and design - Beatrice Rammstedt; Silke Martin; Anouk Zabal; Claus Carstensen; Jürgen Schupp (Large-scale Assessments in Education, 2017)
In Germany, the respondents who had participated in the 2012 survey of the Programme for the International Assessment of Adult Competencies (PIAAC) were re-approached for the panel study PIAAC-L. PIAAC-L aims at investigating the longitudinal effects of skill outcomes over the life course and the development of the key skills assessed in PIAAC. Moreover, additional and alternative background information was collected and analyzed within PIAAC-L. PIAAC-L consists of three follow-up waves to the initial PIAAC 2012 survey. The present paper describes the rationale for PIAAC-L and the benefits of conducting a longitudinal PIAAC follow-up study in Germany. In addition, we outline the general design of PIAAC-L and the specific design of the three waves of data collection. Finally, we address the analytic potential of PIAAC-L data set and its availability to the scientific community.
Keywords: 330; PIACC; PIACC-L; Large-scale assessment; Basic skills; Longitudinal